Respectability, Chivalry and ‘Fixing’ Women: Men’s Narratives of Intimate Partner Violence in Cape Town - Niekerk, Taryn Jill van (Oñati Socio-Legal Series, 2015)
In this paper we argue that social representations are a key mechanism through which knowledge about intimate partner violence is shared and understood. We draw on in-depth interviews with 11 men who had perpetrated violence against an intimate woman partner and analyse the social representations of masculinities, femininities and violence that emerge from men’s narratives about their lives and relationships. We analyse men’s social representations of violence primarily through the lens of respectability involving both masculine and feminine forms of respectability, which contribute to the maintenance of patriarchy. We show how the narrative of respectability is held together by representations of masculine heroism and feminine masochism and the findings cast light on how acts of violence are shaped by a range of intersections and structural oppressions. Social representations of gender and intimate partner violence also show how individual men’s narratives about violence are largely influenced by their peers, kin and wider community norms that make violence against women acceptable.